Effects of UV-B radiation on Lecanicillium spp., biological control agents of the coffee leaf rust pathogen - Galvão, José A. H. [UNESP]; Bettiol, Wagner [UNESP] (Sociedade Brasileira de Fitopatologia, 2014)
Coffee leaf rust is the main disease of coffee and its causal agent is naturally hyperparasited by Lecanicillium lecanii, indicating its potential for biocontrol. Ultraviolet-B (UV-B) radiation is an important factor that interferes on application of biocontrol agents, and Lecanicillium can be affected by UV-B. The objective of this work was to evaluate the effects of UV-B on Lecanicillium isolates and on its capacity to colonize rust lesions. There were variations among Lecanicillium strains in sensitivity to UV-B radiation, causing inactivation and delayed spore germination. The most tolerant strain (CCMA-1143) had LD50=1.63 kJ/m² of UV-B. The incidence and colonization of Lecanicillium on coffee leaf rust lesions were influenced by the dose of UV-B radiation, and were increased when the isolate CCMA-1143 was sprayed on rust lesions. The effects of UV-B should be considered on efficacy studies for the development of biopesticides.
Keywords: Climate change; UV-B; Hemileia vastatrix; biopesticide